Microalgae culture enhancement through key microbial approaches. (December 2017) - Tandon, Puja; Jin, Qiang
Abstract: The demand for biofuels is rising with the growing population and decreasing reserves of petroleum. Indeed the rising population and increasing level of greenhouse gases not only contribute for global warming, but also imparts serious effects on humans and the environment. There is a constant urge to find other alternatives to the petroleum-based products. Of the three generations of biofuel feed stocks i.e. food crops, non-food crops and microalgae-derived biofuels; it is discussed that microalgae can be the best source of feed stock in terms of food security and for reducing the harmful impact on the environment. This paper serves as base to discuss the benefits of using microalgae as a source of biomass for biofuels and the methods that can be used to enhance the microalgal biology in order to improve their production. It reviews how the use of optimized nutrient concentration and culture conditions increase the yield, cell density and lipid productivity. It further reviews the role of bacteria in enhancing/inhibiting the microbial biomass and lipid productivity in microalgal-bacterial biological associations. The final part of the paper lays emphasis on the importance of improving microalgal biology by the use of genetic engineering and metabolic engineering in order to obtain desired results. Overall stress is placed upon unfolding and unraveling the gaps present in producing microalgal biomass, such as inefficient and reduced production, poor penetration of light in dense cultures, low oil content and higher harvesting costs. Overcoming of these major bottlenecks by ecologically engineering species specific valuable microalgal-bacterial mini consortium might lead to specific and noteworthy breakthrough in the production of clean, green, renewable, sustainable and high yielding microalgal biofuel.